Make the invisible visible: Valuation of the hidden cost of particulate-filtering facemask use against air pollution in China. (20th October 2022) - Ma, Xunzhou; Wu, Dan; Wang, Jie; Sun, Fengwei; Li, Zhongdong; Zhang, Ling; Xiao, Yu
Abstract: The use of articulate-filtering facemasks (hereinafter referred to as facemasks) as a defensive measure to reduce air pollution exposure has not been adopted by the Chinese public. Our descriptive investigation reveals hidden barriers other than facemask expenditure that determine the choice to use facemasks. Whether discomfort or inconvenience are the major sources of inaction is largely unknown. By conducting a choice experiment, we observed how people made trade-offs between the costs and health benefits of facemask use in monetary terms, defined as willingness to pay (WTP). The results first demonstrated that discomfort and inconvenience majorly account for the inaction of facemask use, as they are, on average, valuated 6.94 and 24.00 times the facemask expenditures for year 2017 and 2022, respectively. Second, we estimated the threshold of lung cancer mortality above which the cost of facemask use weighs less than the health benefits, which implies a trigger point of health protection behavior. Third, we predicted, in the contexts of air pollution in 2017 and 2021 at the city level, that people refused to wear facemasks if they perceived lung cancer mortality as the one presented in current scientific assessments. We suggested the need to study the subjective reality of public defensive measures if the objectives of air quality and, more generally, environmental management are to be achieved. Highlights: The particulate-filtering facemask use was not advocated during the pollution episodes. People experienced physiological and psychological discomfort and inconvenience when wearing a facemask. The hidden cost was substantially larger than facemask expenditure. The level of lung cancer mortality above which the health benefits outweighed the costs of facemask use is estimated. People would refuse to wear facemasks in the context of air pollution at the city level in 2017.